2005
DOI: 10.1207/s15374424jccp3401_5
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Peer Relations, Friendships, and Romantic Relationships: Do They Predict Social Anxiety and Depression?

Abstract: This study examined multiple levels of adolescents' interpersonal functioning, including general peer relations (peer crowd affiliations, peer victimization), and qualities of best friendships and romantic relationships as predictors of symptoms of depression and social anxiety. An ethnically diverse sample of 421 adolescents (57% girls; 14 to 19 years) completed measures of peer crowd affiliation, peer victimization, and qualities of best friendships and romantic relationships. Peer crowd affiliations (high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

68
701
4
22

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 871 publications
(795 citation statements)
references
References 33 publications
68
701
4
22
Order By: Relevance
“…These include increased loneliness, peer rejection, anxiety, depression and lowered self-esteem (La Greca & Harrison, 2005). Studies have suggested that ETB may lead to increased distress among educators.…”
Section: Consequences Of Etbmentioning
confidence: 99%
“…These include increased loneliness, peer rejection, anxiety, depression and lowered self-esteem (La Greca & Harrison, 2005). Studies have suggested that ETB may lead to increased distress among educators.…”
Section: Consequences Of Etbmentioning
confidence: 99%
“…Је9на о9 DреLDосLавки је и 9а на раном узрасLу вршњаци социјално Dову-чену и анксиозну 9ецу не оDажају као социјално некомDеLенLну, али 9а на сLаријим узрасLима мла9и кажњавају (о9Jацују, зло-сLављају) вршњаке који не Dоказују усмереносL ка вршњачкој :руDи (Younger et al, 1993). ВикLимизација и о9JаченосL о9 вр-шњака, на сLаријим узрасиLма, Dовезани су са већом усамљено-шћу, инLернализованим DроJлемима (Hymel et al, 1990;La Greca & Harrison 2005;Fekkes et al, 2006) и лошијим усDехом у школи (Juvonen et al, 2000) социјално Dовучене 9еце.…”
Section: уводunclassified
“…У скла9у са комлемен-Lарним исLраживањима (Smith et al, 2004), 9оJијени назали су:е-ришу 9а су мла9и са лаком ИО вулнераJилнија :руDа за уло:у жр-Lве не:о мла9и ТР. У Dрило: наве9еном су и сLу9ије које DоLвр-ђују 9а су 9еца и мла9и који у вршњачким конфликLима реа:ују искључиво Dовлачењем (DоDушLање и изJе:авање) Dо Dравилу анксиозни, Jојажљиви, неси:урни, усамљени и неасерLивни (Olweus, 1993;Rubin & Burgess, 2001), о9носно каракLеришу их Dро-Jлеми инLернализовано: сDекLра (Fekkes et al, 2006;La Greca & Harrison 2005). За разлику о9 ученика са лаком ИО, LиDични мла-9и ове Dасивне, несамоDоуз9ане оJлике решавања конфликаLа (AS=21,58 -изJе:авање; AS=20,93 -DоDушLање), као и оминацију (AS=21,96) мање корисLе, а њихов најчешћи изJор је заје ничко ре-шавање конфликаLа (AS=26,58).…”
Section: дискусија резултатаunclassified
“…Nonclinical social anxiety is categorized by social fears, excessive discomfort, negative rumination, and somatic symptoms such as trembling, blushing and sweating before, during, and after social interactions (Heiser, Turner, Beidel, & Roberson-Nay, 2009). Adolescents who are socially anxious tend to be less accepted and victimized by peers (Erath, Flanagan, Bierman, & Tu, 2010;Flanagan, Erath, & Bierman, 2008;La Greca & Lopez, 1998;La Greca & Harrison, 2005;Siegel, La Greca, & Harrison, 2009;Storch, Brassard, & Masia-Warner, 2003), have poor relationships with parents and romantic partners (Hebert, Fales, Nangle, Papadakis, & Grover, 2013), and are often lonely (Stoeckli, 2010). For socially anxious adolescents, online chatting may be a viable alternative to an unsatisfactory or maybe even non-existing social life offline.…”
Section: Introductionmentioning
confidence: 99%